Easter Week Visit to Albert Watkins and Rose Watkins in Huntington Beach - Watkins, Howard::::::::: (1984)
Robin Watkins in blue umbrella stroller accepting bite of food from Rose Watkins Cassette radio and intercom unit on corner table; 207 Geneva Avenue #1